Peran Orangtua dalam Proses Belajar Anak di Rumah pada Masa Pandemi Covid-19 (Studi Kasus di SDN Lendang Ara Kecamatan Kopang) - Umami, Satria (Lembaga Yasin AlSys, 2021)
The purpose of this study is to determine the role of parents in accompanying children in the learning process during the covid-19 pandemic era and to determine the supporting and inhibiting factors that affect the learning process of children in the covid-19 pandemic era. In the study, the data obtained in the field used documentation and interview observation. The purpose of this study is to determine the role of parents in accompanying children in the learning process during the covid-19 pandemic and to determine the supporting and inhibiting factors that affect the learning process of children in the covid-19 pandemic era. In the study, the data obtained in the field used documentation and interview observation. The research method used in this research is qualitative research with a case study approach with data collection methods through two, namely primary data and secondary data, by collecting from journals, books, and archives related to the research objectives by accurate data. The results of research on the role of perents in the learning process of children at home during the covid-19 pandemic era show that parents are the main responsibility for their children’s education of their children. In the era of the covid-19 pandemic, currently parents have a very important role in providing motivation to children because in the teaching and learning process carred out online, the child becomes overwhelmed, coufused and sometimes the student experiences boredom.